(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical characteristics, ultrasound imaging, and surgical outcomes of cryptorchidism in the inguinal canal in children at Thai Nguyen Central Hospital. Subjects and Methods: We conducted a study on 85 patients who underwent surgery, involving 102 testes descended to the scrotum, from January 2020 to March 2024 at the Pediatric Surgery Department of Thai Nguyen Central Hospital. Results: The average age of surgery was 3.64 ± 2.828 years, with the youngest being 1 and the oldest 12. The most common age group was 1- ≤5 years, accounting for 82.3%. Ultrasound detected 100% of the cases of undescended testes in the inguinal canal, with the most common location being in the inguinal canal (52.94%). All patients underwent open surgery to lower the undescended testes into the scrotum. The average surgery duration was 40.24 ± 6.326 minutes, and the average postoperative recovery time was 3.4353±1.051 days. Post-surgery, 82.4% of testes were positioned in the scrotum, while 17.6% were at the base of the penis. The TAI improved after surgery compared to pre-surgery levels. Conclusion: Surgery for undescended testes in the inguinal canal is safe and yields good treatment outcomes.